DAMPAK KOMPENSASI TERHADAP KINERJA PEGAWAI KANTOR PENGADILAN AGAMA TANGGAMUS - Betty Magdalena (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
Forming of working motivation is formed by conducive working environment developmentsan entry point in development and management. Then, compensation given well and straight to thepoint is one thing which is not able to be separated from the effort of building the employeemotivation to support the institution performance in order to be able to do the duty and the functionwell.Compensation becomes important to be used by employees in full fill the needs as one ofthe effort for increasing the prosperous of employee itself. The increasing of Tanggamus ReligionCourt performance as one of instrument of Tanggamus Religion Court Government in full filldevelopment financial aspects that is an injury need to full fill development management targetsbased on District Autonomy Management. It will be a problem which comes from inside or outside ofReligion Court Institution. The purpose of this research is to know how big the influence ofcompensation toward employee performance increasing in Tanggamus Religion Court surrounding.The result of this research that there is a correlation between Compensation variable toPerformance of Tanggamus Religion Court Employees calculated by coefficient correlation is 0,643.It shows that good enough correlation (above 0,5) between compensation is received by employeeswith Performance of Tanggamus Religion Court Employees.